Development of E-module Internet of Things (IoT) Antares by PT. Telkom Indonesia Based on Science, Technology, Engineering, and Mathematics (STEM) for Vocational High School Students - Fadil, Muhammad Anwar; Mukhidin, Mukhidin; Elvyanti, Siscka (MO.RI Publishing, 2023)
This research is motivated by a needs analysis among teachers and students at SMK Negeri 4 Bandung. From the distribution of a needs analysis questionnaire in the class XII TOI-1, it was found that 85% of students expressed a strong need for a STEM-based IoT e-module, with a high level of agreement on its development. Similarly, it was revealed that teachers also strongly require a STEM-based IoT e-module, with 95% agreeing on its necessity. To develop the STEM-based IoT E-module, Flip Pdf Professional application was utilized. The aim of this research and development was to describe the process of developing the E-module and to understand the responses of teachers and students to the e-module. The research method employed was R&D (Research and Development) using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The result of this research was the successful development of a STEM-based IoT e-module through the ADDIE development model. The feedback from teachers reached 95.63%, falling into the